An axis-biased approach for dead reckoning algorithm - Tan, Ping Teck (2017)
This report aims to improve upon the conventional Dead Reckoning algorithm. The conventional Dead Reckoning may not work perfectly with entities which move in a curvilinear motion. The axis biased approach was proposed as a solution to this limitation. Using Unreal Engine 4 to generate the character’s in-game path, simulation of Dead Reckoning was done on the coordinates for comparison between the two models. Biased Dead Reckoning cycles through three different options of no bias, x-axis bias and y-axis bias. This solution had a trade-off, introducing more errors while reducing the average deviation from actual path.